Attitude, Skills Performance, and Implications of Using Simulator Programs among Marine Engineering Students - Alimen, Rolando A.; Ortega, Nilo B.; Pador, Ralph L. (JPAIR Multidisciplinary Research, 2010)
This study aims to determine the attitude towards, skills performance, and implications of simulator programs among marine engineering students of John B. Lacson Foundation Maritime University-Molo, Iloilo City, Philippines. The participants of this study were the 120 marine engineering students who used simulator programs in their subject, specifically Power Plant 1. This present study employed quantitative-qualitative method of gathering data. Data gathered were obtained through Likert-type data-gathering instrument entitled "Attitude towards Simulator Programs," assessment rating instrument of the professors teaching simulator was used to determine the skills performance of the students, and implications of using simulator programs were determined by using the students' qualitative inputs on simulator. Appropriate statistical tools were used to analyze the quantitative data. Interviews and comments were used for qualitative analysis of the study. Results of this study were properly disseminated and discussed among faculty members handling simulator programs. Department heads, faculty members, and students were invited to the presentation of the results of this study to discuss the effect as regards their academic performance.
Keywords: Attitude; skills performance; implications; simulator program; Marine Engineering students